Optimized allocation of sectionalizing switches and control and protection devices for reliability indices improvement in distribution systems - Da Silva, Luis Gustavo Wesz [UNESP]; Pereira, Rodrigo Apaecido Fernandes [UNESP]; Mantovani, José Roberto Sanches [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2004)
Reliability of power supply is related, among other factors, to the control and protection devices allocation in feeders of distribution systems. In this way, optimized allocation of sectionalizing switches and protection devices in strategic points of distribution circuits, improves the quality of power supply and the system reliability indices. In this work, it is presented a mixed integer non-linear programming (MINLP) model, with real and binary variables, for the sectionalizing switches and protection devices allocation problem, in strategic sectors, aimed at improving reliability indices, increasing the utilities billing and fulfilling exigencies of regulatory agencies for the power supply. Optimized allocation of protection devices and switches for restoration, allows that those faulted sectors of the system can be isolated and repaired, re-managing loads of the analyzed feeder into the set of neighbor feeders. Proposed solution technique is a Genetic Algorithm (GA) developed exploiting the physical characteristics of the problem. Results obtained through simulations for a real-life circuit, are presented. © 2004 IEEE.
Keywords: Genetic algorithms; Protection system of networks; Reliability; Restoration; Electric power distribution; Electric power system protection; Electric switches; Electronic equipment; Nonlinear programming; Optimization; Distribution circuits; Optimized allocation; Protection devices; Electric power systems